Serambi Maya: Development of a Virtual Application for Exploring Malaysian Traditional Village Games - JAMALUDDIN, DZULKARNAIN; A HAMID, RAHAYU (Applied Information Technology And Computer Science, 2026)
The decline in popularity of Malaysian traditional village games among younger generations has raised concerns about cultural preservation in the digital age. This project, Serambi Maya, addresses this issue by developing a virtual reality (VR) application that offers an immersive and interactive exploration of traditional games such as Guli, Galah Panjang, Baling Selipar, and Batu Seremban. By leveraging the TRES-D methodology, the application integrates authentic cultural settings, gameplay mechanics, and educational content to engage users aged 13 to 30. The VR environment is designed to simulate hands-on experiences while providing historical context and gameplay tutorials in Bahasa Melayu, ensuring cultural relevance and accessibility. Usability and user acceptance were evaluated through functional testing and the System Usability Scale (SUS), with results indicating positive user engagement and satisfaction. This initiative not only revitalizes interest in traditional games but also contributes to the preservation of Malaysia’s cultural heritage through innovative digital means.